2013
DOI: 10.1080/10498850.2013.766293
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surimi-to-Silver Catfish Ratio and Potato Starch Concentration on the Properties of Fish Sausage

Abstract: This study examined the effects of different surimi-to-silver catfish ratios (0/100, 20/80, 40/60, 60/40, 80/20, and 100/0) and potato starch concentrations (3, 5, and 7%) on the properties of fish sausage. The surimi-to-catfish ratio affected the moisture, fat, protein, and ash content of the sausage; as well as cooking loss, greenness, lightness, and hardness. Different concentrations of potato starch affected carbohydrate content, springiness, and yellowness. The most acceptable formulation was the 40/60 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The sensorial scores of the anchovy sausages were higher compared to those reported for other fish sausages. The sensorial scores of Nile tilapia sausage (7.1) and fish sausage made from surimi and silver catfish (4.6-6.8) were found to be lower than 8 (Amiza and Ng, 2015;Dallabona, et al, 2013).…”
Section: Sensorial Propertiesmentioning
confidence: 82%
“…The sensorial scores of the anchovy sausages were higher compared to those reported for other fish sausages. The sensorial scores of Nile tilapia sausage (7.1) and fish sausage made from surimi and silver catfish (4.6-6.8) were found to be lower than 8 (Amiza and Ng, 2015;Dallabona, et al, 2013).…”
Section: Sensorial Propertiesmentioning
confidence: 82%
“…The smell, color, shape and taste of each sample were evaluated. 10 2.5.2 Electronic nose analysis. Electronic nose was performed according to Tian.…”
Section: Flavor Characteristicsmentioning
confidence: 99%
“…Yu et al 7 demonstrated that the breaking force, the breaking distance, and the gel strength of the blended silver carp and the golden threadn bream (Nemipterus virgatus) surimi were signicantly higher than those of single surimi-based product. Amiza et al 10 mixed surimi and silvery catsh in a 40 : 60 ratio to generate a pure surimi gel cost-effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Paker and Matak () added sarcoplasmic proteins extracted from H. molitrix into Alaskan pollock surimi, and found that both the brightness and whiteness of the mixed surimi gel were greater than that of sarcoplasmic protein mixed with myofibrillar protein. Amiza and Ng () mixed common surimi (Grade SA) with silver catfish at ratio of 40:60, and showed that the mixed surimi product had the gel‐forming properties of surimi alone, at a reduced cost. Kobayashi mixed refined fish proteins with fish meat or fish protein solutions from different sources, simplifying the surimi system into a protein system, allowing a more direct analysis of the synergistic gelation effect among fish species (Kobayashi & Park, ).…”
Section: Introductionmentioning
confidence: 99%